As disputas na formação da Argentina: facundo e a negação dos povos autóctones na construção do Estado Nacional (1810-1850) - Katinskas, Guilherme Periotto (2023)
The following Dissertation for the Master's degree proposes to study the work "Facundo: civilization and barbarism" by Domingos Faustino Sarmiento, in this analysis, I seek to understand the influence of the work, of a literary nature in the formation of the National State, in a context of constitution in the 19th century XIX. As the main issue, I seek to present the various projects focused on the denial of land inheritances, emphasizing the negative role of barbarisms coming mainly from native peoples, which defined, in different ways and at different times, these agents as synonyms of delays in liberal civilizational paths . This research proposes to understand, from Sarmiento's texts, their echoes in society and their reception by the public and, within this universe, to understand how the process of denial of indigenous populations was constructed, based on a racialist discourse originating from Sarmiento and other intellectuals, a mentality that was crucial in the creation of the Argentine National State. Thus, in a broader context, here is undertaken a survey of the projects that enabled the consolidation of a homogenizing discourse, where the focus of analysis is the natives, and their participation in the newly formed nation. To this end, it will be crucial to understand how culture, in a broad sense, crystallizes the image of the native population as an antinomy of civilization, imposing on them the figure of barbarians. In order to better define this problem, I encompass the entire process of formulation and construction of what became known as Argentina, observing the echoes of the 1810 revolution until the definitive consolidation of the State. The central figure, however, is the native population of the Pampas, and the process that led to their extermination; which concluded in the 1950s the rise of the 1937 generation to power and the first echoes of a modernization that would come later in the 1890s. The present work, therefore, consists of identifying two problems that permeate fiction and affect other important fields, such as biology and economics. The hypothesis is that the crossing of different negation projects and different perspectives in relation to indigenous populations, were first articulated in the novels, allowing us to think about the multiple relationships between literature and history that were being formulated, in particular, by the crossing of literature and epistemology in a broader sense. It is important to point out that the fictions addressed participate in the condition 12 of being on the cultural frontiers and on the frontiers of fiction. Thus, they present points of contact. In the reflection on the concept of representation, the two narratives impose themselves in an ambivalent position between fiction and non-fiction, whose objective was to position the logic of the natives of the land according to the project of the criollos for these populations, within a long period of time. transculturation process